Structural features underlying T-cell receptor sensitivity to concealed MHC class I micropolymorphisms. - Stewart-Jones, G; Simpson, P; van der Merwe, P; Easterbrook, P; Mcmichael, A; Rowland-Jones, S; Jones, E; Gillespie, G (2012)
Polymorphic differences distinguishing MHC class I subtypes often permit the presentation of shared epitopes in conformationally identical formats but can affect T-cell repertoire selection, differentially impacting autoimmune susceptibilities and viral clearance in vivo. The molecular mechanisms underlying this effect are not well understood. We performed structural, thermodynamic, and functional analyses of a conserved T-cell receptor (TCR) which is frequently expanded in response to a HIV-1 epitope when presented by HLA-B*5701 but is not selected by HLA-B*5703, which differs from HLA-B*5701 by two concealed polymorphisms. Our findings illustrate that although both HLA-B*57 subtypes display the epitope in structurally conserved formats, the impact of their polymorphic differences occurs directly as a consequence of TCR ligation, primarily because of peptide adjustments required for TCR binding, which involves the interplay of polymorphic residues and water molecules. These minor differences culminate in subtype-specific differential TCR-binding kinetics and cellular function. Our data demonstrate a potential mechanism whereby the most subtle MHC class I micropolymorphisms can influence TCR use and highlight their implications for disease outcomes.